2020
DOI: 10.1186/s12913-020-05101-z
|View full text |Cite
|
Sign up to set email alerts
|

When patients decide the admission – a four year pre-post study of changes in admissions and inpatient days following patient controlled admission contracts

Abstract: Background: Mental health professionals usually decide patients' access to inpatient care to ensure the rational and fair distribution of care based on need and prognosis. The purpose of the current study is to investigate the effects of increasing patients' influence on admission by enabling patients to initiate brief inpatient stays of up to five days at a community mental health center. Patients can initiate admission according to their own discretion, outside the existing referral and gatekeeping system. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
2
8
0
1
Order By: Relevance
“…A small RCT [ 5 ] and a propensity-matched study of PCAs [ 3 ] showed a significant reduction in inpatient days in both controls and PCA patients. In these studies, PCA use was lower or the inpatient days reduction was smaller, indicating differences in service or implementation compared to previous Norwegian studies [ 6 ]. In any case, none of the published studies have yet reported increased use of inpatient days or other important problems for the patients or wards following PCA introduction, thus indicating non-inferiority for PCAs [ 6 ].…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…A small RCT [ 5 ] and a propensity-matched study of PCAs [ 3 ] showed a significant reduction in inpatient days in both controls and PCA patients. In these studies, PCA use was lower or the inpatient days reduction was smaller, indicating differences in service or implementation compared to previous Norwegian studies [ 6 ]. In any case, none of the published studies have yet reported increased use of inpatient days or other important problems for the patients or wards following PCA introduction, thus indicating non-inferiority for PCAs [ 6 ].…”
Section: Introductionmentioning
confidence: 67%
“…Findings in this study are from the subjective perspective of the patients, and we did not collect family carers or provider evaluations. We have previously reported changes in inpatient day use for a subsample of this study [ 6 ]. We had no control group rating regular admissions, so we could not make comparisons to treatment as usual.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations